Responding Crisis Communication: The Role of Social Media in Building Brand Trust - Yuliani Dewi Risanti; Frila Nurfadila (CV. Ulil Albab Corp, 2025)
Previous research shows that reputation and image is very important to the continuity and sustainability of the organizations. Recently, it can be easily damaged by the uncontrolled message circulation that spread on social media. Consumers tend to mislead by untrusted source of information causing losing their trust and give immediate impact to sales decline. One of the vulnerable industry that regularly facing this situation is in food and beverage. Dough Lab that known for their artisan cookies products as the object of this case study has to deal with the incident which video spread on social media that went viral within second. This study aims to examine in how Dough Lab respond the crisis that can lead to damage reputation by utilizing social media as source of information to external stakeholders in particular customers. Data collections through depth interview with the representative of corporate communications of the company supported by literature and previous research. Results shows the social media are able to be an essential role in responding crisis communications since they can be as source of information of the company to the stakeholders. However, their credibility is being considered since it delivered in their official social media which can fully controlled by the company. After all, the company should maintain to communicate transparent with the consumers and raise public intention to create user generated content to increase the credibility of the message and source of information.